(untitled) (The Agriculturists, 2014)
Eight heat tolerant CIP (International Potato Centre) potato genotypes along with BARI (Bangladesh Agricultural Research Institute) Alu-7 (Diamant) and one local variety (Dohazari Sada) were evaluated at Agricultural Research Station, Pahartali, Chittagong during 2011-12 to identify heat tolerant genotypes from varieties and CIP clones of potato. Diamant and Dohazari Sada and all the heat tolerant CIP genotypes were found to grow well up to 60 DAP (days after planting) against heat having healthy plants and no senescence was noticed. After that 61-100% plants died due to high temperature (29.8oC) depending on the genotypes. Genotype CIP 139 gave the highest yield (14.18 t/ha) and was comparatively less affected by heat than the other genotypes. The high dry matter (22.43 %) accumulated in the local variety Dohazari Sada. DOI: http://dx.doi.org/10.3329/agric.v12i1.19580 The Agriculturists 2014; 12(1) 50-55